Proposals for Next-Generation Eco-Friendly Non-Flammable Refrigerants for a −100 °C Semiconductor Etching Chiller Based on 4E (Energy, Exergy, Environmental, and Exergoeconomic) Analysis - Hye-In Jung; Chang-Hyo Son; Joon-Hyuk Lee (Energies)
Recent advancements in cryogenic etching, characterized by high aspect ratios and etching rates, address the growing demand for enhanced performance and reduced power consumption in electronics. To precisely maintain the temperature under high loads, the cascade mixed-refrigerant cycle (CMRC) is predominantly used. However, most refrigerants currently used in semiconductor cryogenic etching have high global warming potential (GWP). This study introduces a −100 °C chiller using a mixed refrigerant (MR) with a GWP of 150 or less, aiming to comply with stricter environmental standards and contribute to environmental preservation. The optimal configuration for the CMRC was determined based on a previously established methodology for selecting the best MR configuration. Comprehensive analyses—energy, exergy, environmental, and exergoeconomic—were conducted on the data obtained using Matlab simulations to evaluate the feasibility of replacing conventional refrigerants. The results reveal that using eco-friendly MRs increases the coefficient of performance by 52%, enabling a reduction in compressor size due to significantly decreased discharge volumes. The exergy analysis indicated a 16.41% improvement in efficiency and a substantial decrease in exergy destruction. The environmental analysis demonstrated that eco-friendly MRs could reduce carbon emissions by 60%. Economically, the evaporator and condenser accounted for over 70% of the total exergy costs in all cases, with a 52.44% reduction in exergy costs when using eco-friendly MRs. This study highlights the potential for eco-friendly refrigerants to be integrated into semiconductor cryogenic etching processes, responding effectively to environmental regulations in the cryogenic sector.